Magnetically inspired deformation of the liquid/vapor interface drives soap bubbles. Issue 4 (6th August 2018) - Legchenkova, Irina; Chaniel, Gilad; Frenkel, Mark; Bormashenko, Yelena; Shoval, Shraga; Bormashenko, Edward
Abstract : The possibility of driving millimetrically scaled, soap and glycerol bubbles floating on a liquid, using a steady magnetic field of c. 0·5 T, is demonstrated. The bubbles are repelled by the magnet, starting from a threshold initial lateral distance of L 0 cr = 4 mm from the vertical axis of the magnet, and are attracted to the magnet when the initial lateral distance L 0 < L 0 cr . The displacement of bubbles is due to the deformation of the liquid/vapor interface by the magnetic field, known as the Moses effect. This deformation gives rise to the change in apparent contact angles driving the bubble. Switching of repulsion to attraction is explained in terms of a model of an interaction between two capillary charges, one of which represents the bubble and the second represents the well, produced by the magnet on the liquid/vapor interface. The experiments with bubbles demonstrate that the role of gravity in the displacement of floating diamagnetic objects driven by steady magnetic fields may be negligible. The mathematical model of the process is suggested. The experimental data are well explained by the proposed model.